Mechanical stimuli such as shear stress and piezo1 stimulation generate red blood cell extracellular vesicles - Sangha, Gurneet S.; Weber, Callie M.; Sapp, Ryan M.; Setua, Saini; Thangaraju, Kiruphagaran; Pettebone, Morgan; Rogers, Stephen C.; Doctor, Allan; Buehler, Paul W.; Clyne, Alisa M. (Frontiers in Physiology, 2023)
Generating physiologically relevant red blood cell extracellular vesicles (RBC-EVs) for mechanistic studies is challenging. Herein, we show that RBC-EVs can be generated at high concentrations in vitro via shear stress and mechanosensitive piezo1 ion channel stimulation. We further determined how RBC-EV generation parameters (hematocrit, treatment time, and treatment dose) and isolation methods (membrane-based affinity, ultrafiltration, and ultracentrifugation with and without size exclusion chromatography) can be tuned to improve RBC-EV yield and purity. We now show that treating RBCs at 6% hematocrit with 10 µM piezo1-agonist yoda1 for 30 minutes and isolating RBC-EVs via ultracentrifugation minimized hemolysis, maximized yield and purity, and produced the most consistent RBC-EV preparations. RBC-EV vascular phenotype, assessed via pressure myography, showed that co-isolated contaminants, but not piezo1 RBC-EVs, induced mouse carotid artery vasodilation. This work emphasizes the importance of characterizing EV purity before mechanistic analysis and suggests that RBC-EVs may be generated under physiologic flow conditions.